Phenotypic and marker aided identification of donors for spot blotch resistance in Wheat - Singh, Gyanendra; Sheoran, Sonia; Chowdhury, A K; Tyagi, B S; Bhattacharya, P M; Singh, Virender; Ojha, Ashish; Turan, Rajita; Sharma, Indu (Journal of Cereal Research, 2014)
In this study, multi-locational phenotypic data for spot blotch disease and other agronomic traits of two mapping populations (set-I: Sonalika / BH1146, set-II: Kanchan / Chirya1) generated over two consecutive years (2011-2013) was utilized for identifying potential lines possessing spot blotch resistance. Some promising lines (seven lines in set-I and six lines in set-II mapping populations) based on the performance for resistance and other agronomic traits (days to heading, plant height, spike length and thousand grains weight) were shortlisted and further validated using molecular markers. Diagnostic markers for spot blotch (Xgwm371, Xgwm425, Xgwm445) and SSR markers (Xbarc59, Xbarc232) associated with percent disease severity identified during preliminary RILs screening were also used to validate these lines for spot blotch resistant. These lines have potential and thus could be utilized for direct testing or as improved donor to incorporate spot blotch resistance in wheat. Â